Numerical Calculation of Meridional Path Line and Optimum Approximation with Multi-segment Arc of Hydrodynamic Torque Converter - Liu Shiping; Zhang Zongfu; Zhang Zhihua; Jia Jiantao (Jixie chuandong)
The modeling precision of hydraulic torque converter is investigated and various factors affect the modeling precision are analyzed,a new high precision modeling method is proposed. Based on the meridional path line equation,the calculation formula of curvature radius and curvature center coordinates is derived.By using numerical calculation method,the curves of curvature radius and curvature center coordinates versus the polar angle are obtained. According to this law,by using a non-elementary function multi-section circular arcs uniformly approximation,the maximal absolute error of approximation reaches a minimum. A parametric program code is developed and all equations are verified. By using the program,the radius and center coordinates of each circular arc,and polar angle of each arc joining point are obtained directly. In addition,the absolute error and percentage error of approximation can be obtained as well,which is convenient to discriminate if the approximation meets the precision requirement. The investigation results indicate that the method is feasible,can improve modeling accuracy significantly,and is of engineering application value.